THE INFLUENCE OF PROFUNDA POPLITEAL COLLATERAL INDEX ON THE RESULTS OF PROFUNDOPLASTY - Horlenko, F. V. (Проблеми клінічної педіатрії, 2019)
Abstract. Introduction. In order to eliminate chronic ischemia, perform direct and indirect reconstruction operations. The choice of surgical treatment for patients with obliteration atherosclerosis of the vessels of the lower extremities is one of the most difficult problems in vascular surgery. The purpose of the study: to evaluate the results of profundoplasty, depending on the magnitude of the deepjaw and popliteal index. Material and Methods. The results of the 124 patients treatment, which were operated in the department of vascular surgery of Zakarpattia Regional Clinical Hospital named after M.Sc. Andriy Novak during the period from 2005 to 2018. The patients had the following diagnosis distal forms of lower extremities lesion of arteries of the by chronic lower limb ischemia. Results. Patients after profundoplasty were divided into 3 groups depending from the size of the Profundapopliteal collateral index (PPCI). PPCI in the Group I patients (the 5-year limb preservation) was 74.2%, in Group II patients - 51.8% and in Group III patients - 23.4% according of the study result with using profundoplasty. Conclusion. PPCI which characterized by the collateral system development degree of the popliteal-pedicel segment, is considered to be useful for selecting of the optimal revascularization procedures for the saving limbs.